2008
DOI: 10.1152/ajpendo.90482.2008
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and cardiac myopathy in HIV-1 transgenic rats

Abstract: The mechanism by which human immunodeficiency virus (HIV)-1 infection in humans leads to the erosion of lean body mass is poorly defined. Therefore, the purpose of the present study was to determine whether transgenic (Tg) rats that constitutively overexpress HIV-1 viral proteins exhibit muscle wasting and to elucidate putative mechanisms. Over 7 mo, Tg rats gained less body weight than pair-fed controls exclusively as a result of a proportional reduction in lean, not fat, mass. Fast- and slow-twitch muscle at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
(94 reference statements)
4
17
0
Order By: Relevance
“…This time course is comparable with other rodent studies where an atrophic response to castration has been demonstrated (10). Body composition, i.e., body fat and LBM, was measured using 1 H nuclear magnetic resonance (NMR) (LF90 Minispec; Bruker, The Woodlands, TX) (46). An oral glucose tolerance test (OGTT) was performed at the end of the 7th week on overnight-fasted rats.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…This time course is comparable with other rodent studies where an atrophic response to castration has been demonstrated (10). Body composition, i.e., body fat and LBM, was measured using 1 H nuclear magnetic resonance (NMR) (LF90 Minispec; Bruker, The Woodlands, TX) (46). An oral glucose tolerance test (OGTT) was performed at the end of the 7th week on overnight-fasted rats.…”
Section: Methodssupporting
confidence: 75%
“…At the start of the final week of the study, rats were housed individually in metabolic cages and acclimated for 24 h. During the subsequent 24-h period, urine was collected and an aliquot used for HPLC determination of 3-methylhistidine (3-MH) and data normalized to the urinary creatinine concentration (46). 3-methylhistidine is formed by posttranslation modification of histidine released from actin and myosin and provides an in vivo estimate of myofibrillar protein breakdown (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart function was assessed by echocardiography using the Sequoia C256 Echocardiography System (Siemens Medical Solutions, Mountain View, CA) equipped with a 7.5-MHz transducer, as described (62). Rats were lightly anesthetized by the intraperitoneal injection of the combination of ketamine (40 mg/kg) and xylazine (1 mg/kg), and body temperature was maintained by heating pad.…”
Section: Methodsmentioning
confidence: 99%
“…Using a non-replicative, non-infectious HIV-1 transgenic rat model, chronic expression of HIV-1-related proteins causes atrophy in gastrocnemius, plantaris and soleus muscles with a concomitant increase in MAFbx, but not in MuRF1, mRNA [82,89]. A common treatment for HIV involves the use of various HIV protease inhibitors such as indinavir.…”
Section: Hiv/aidsmentioning
confidence: 99%